ANALISIS PENGGUNAAN KATA BAKU DAN TIDAK BAKU DIKALANGAN GEN ALPHA DI KELAS VIII SMP NEGERI 2 SUNGGAL - Roma Asi Siahaan, Perida; Catur Widana, Haryasa; Purba, Murni; Sasna Junaidi, Nurhikmah; Br Barus, Depita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the use of standard and non-standard words in daily communication among Generation Alpha. Generation Alpha, defined as individuals born from 2010 to the present, has grown up in a digital era that is strongly influenced by social media, technology, and internet culture. This condition is believed to affect their language habits, including their choice of word forms. This study employs a qualitative descriptive method, with data collected through observation and interviews with a number of elementary and junior high school students at SMP Negeri 2 Sunggal. The collected data were analyzed based on linguistic rules outlined in the Great Dictionary of the Indonesian Language (Kamus Besar Bahasa Indonesia/KBBI) to identify forms of standard and non-standard words used and their contexts of usage. The results of this study are expected to provide an overview of patterns of Indonesian language use among Generation Alpha and to serve as a consideration for more contextual Indonesian language development and instruction in the digital era.